2014
DOI: 10.1103/physrevb.90.014107
|View full text |Cite
|
Sign up to set email alerts
|

Surface polarization, rumpling, and domain ordering of strained ultrathinBaTiO3(001) films with in-plane and out-of-plane polarization

Abstract: BaTiO 3 ultrathin films (thickness ≈ 1.6 nm) with in-and out-of-plane polarization are studied by first-principles calculations. Out-of-plane polarization is simulated using the method proposed by Shimada et al. [Phys. Rev. B 81, 144116 (2010)], which consists in building a supercell containing small domains with alternating up and down polarization. This allows one to investigate the properties of defect free BaTiO 3 ultrathin films with polarization perpendicular to the surface, as a function of in-plane la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
(61 reference statements)
2
18
0
Order By: Relevance
“…This geometry allows us to obtain in a single calculation the relevant electronic quantities of both electrode/P + and electrode/P − interfaces for the out-of-plane direction of the ferroelectric polarization. It also avoids the well-known issue of how to realistically screen free ferroelectric surfaces in finite supercells [34]. Of course, this approach does not offer information on the relaxation mechanisms, rumpling, or other surface effects, but within this paper we are mostly concerned with the interface properties, and our treatment gives insight into the LSMO/BTO interface region [6,7,30].…”
Section: Computational Detailsmentioning
confidence: 99%
“…This geometry allows us to obtain in a single calculation the relevant electronic quantities of both electrode/P + and electrode/P − interfaces for the out-of-plane direction of the ferroelectric polarization. It also avoids the well-known issue of how to realistically screen free ferroelectric surfaces in finite supercells [34]. Of course, this approach does not offer information on the relaxation mechanisms, rumpling, or other surface effects, but within this paper we are mostly concerned with the interface properties, and our treatment gives insight into the LSMO/BTO interface region [6,7,30].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The BTO films grown on a STO substrate have a compressive strain of 2% at the interface. As a result, the film is expected to stay in a single tetragonal phase below the ferroelectric phase transition [37,38]. Tetragonal BTO can host a ferroelectric polarization along the 001 out-of-plane as well as the 100 and 010 in-plane directions.…”
Section: Wannier-stark Localizationmentioning
confidence: 99%
“…In films, the transition temperature is raised for compressive as well as tensile strain [35]. For tensile strain, it has been demonstrated that solely an orthorhombic phase exists below the ferroelectric transition temperature [35][36][37]. For compressive strain, the tetragonal phase [ Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BaTiO 3 /SrTiO 3 and PbZrO 3 /SrZrO 3 (0 0 1) interfaces present an excellent possibility for developing novel materials with outstanding properties, as well as they are extremely important in studying the fundamental physics of ferroelectric materials. Despite the huge technological importance of SrTiO 3 (STO), BaTiO 3 (BTO), SrZrO 3 (SZO) and PbZrO 3 (PZO) perovskites, and numerous ab initio studies of their (0 0 1) surfaces, [1][2][3][4][5][6][7][8][9][10][11][12][13], it is hard to understand, why only a small amount of ab initio and experimental studies exist dealing with BTO/STO (0 0 1) interface [14][15][16][17][18][19]. There are no experimental studies available, and only single ab initio calculation [20] exist dealing with PZO/SZO (0 0 1) interface.…”
Section: Introductionmentioning
confidence: 99%